2017
DOI: 10.18488/journal.8.2017.53.233.244
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exchange Rates in Somalia

Abstract: Article HistoryThe purpose of this paper is to investigate the factors that determine exchange rates in Somalia and how those factors influence the exchange rates. To examine the relationship, a Monetary Approach to Exchange rate is employed to estimate the effects of trade balance, money supply, external debt and lack of government on exchange rate in Somalia for the period from 1970 to 2014 using MRA under OLS method. Main findings indicate that trade balance, money supply and external debt has a negative si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…The empirical results tested by OLS which implies that if relative price levels increase by one, the value of Thai baht per one U.S. dollar rises by 11.0057, holding other factors constant. This result is similar toIsse & Ibrahim (2017), in which they examined that inflation is not substantial to the exchange rate. However,Hsieh (2009),Chaiphat (2017) andLi et al (2019) found that the larger inflation differential causes the changes in their home currencies.The domestic interest rate is significant at 1% because its p-value is 0.0000.…”
supporting
confidence: 82%
“…The empirical results tested by OLS which implies that if relative price levels increase by one, the value of Thai baht per one U.S. dollar rises by 11.0057, holding other factors constant. This result is similar toIsse & Ibrahim (2017), in which they examined that inflation is not substantial to the exchange rate. However,Hsieh (2009),Chaiphat (2017) andLi et al (2019) found that the larger inflation differential causes the changes in their home currencies.The domestic interest rate is significant at 1% because its p-value is 0.0000.…”
supporting
confidence: 82%